2019
DOI: 10.7717/peerj.6387
|View full text |Cite
|
Sign up to set email alerts
|

Motor expertise modulates unconscious rather than conscious executive control

Abstract: BackgroundExecutive control, the ability to regulate the execution of a goal-directed task, is an important element in an athlete’s skill set. Although previous studies have shown that executive control in athletes is better than that in non-athletes, those studies were mainly confined to conscious executive control. Many recent studies have suggested that executive control can be triggered by the presentation of visual stimuli without participant’s conscious awareness. However, few studies have examined uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…In addition, the analysis of the divers' training time and RDD showed that the longer their diving training, the larger the RDD they produced, especially for suprasecond durations. This result is consistent with the suggestions of some researchers that athletes' cognitive advantage in expertise-related tasks is mainly practice dependent and cannot be attributed to innate differences (Meng et al 2019;Yarrow et al 2009). In the case of the divers, a longer sport-specific training period resulted in more efficient information processing with regard to expertise-related stimuli, and this more efficient information extraction led these athletes to reproduce a longer duration for expertise-related stimuli than for general stimuli.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the analysis of the divers' training time and RDD showed that the longer their diving training, the larger the RDD they produced, especially for suprasecond durations. This result is consistent with the suggestions of some researchers that athletes' cognitive advantage in expertise-related tasks is mainly practice dependent and cannot be attributed to innate differences (Meng et al 2019;Yarrow et al 2009). In the case of the divers, a longer sport-specific training period resulted in more efficient information processing with regard to expertise-related stimuli, and this more efficient information extraction led these athletes to reproduce a longer duration for expertise-related stimuli than for general stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, You et al (2018) found that table tennis players outperformed nonathletes in regard to response inhibition even in an unconscious condition where the participants were unaware of the stimulus in the task. Moreover, the findings of Meng et al (2019) also suggest that motor expertise modulates unconscious executive control and is positively correlated with unconscious executive control in table tennis players. These results, combined with the fact that divers, similar to many athletes in open-skill sports, must perform complex movements under high time pressure, suggest that the efficient information processing conferred by their cognitive advantages affects subsecond-duration processing, which is considered to be dominated by automatic or unconscious mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the analysis of the divers' training period and RDD showed that the longer their diving training, the larger the RDD they produced, especially for suprasecond durations. This result is consistent with the suggestions of some researchers that athletes' cognitive advantage in expertise-related tasks is mainly practice dependent and cannot be attributed to innate differences (Meng et al, 2019;Yarrow, Brown & Krakauer, 2009). In the case of the divers, a longer sport-specific training period resulted in more efficient information processing with regard to expertise-related stimuli, and this more efficient information extraction led these athletes to reproduce longer durations for expertise-related stimuli than for general stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, You et al (2018) found that table tennis players outperformed nonathletes in regard to response inhibition even in an unconscious condition where the participants were unaware of the stimulus in the task. Moreover, the findings of Meng et al (2019) also suggested that motor expertise modulates unconscious executive control in table tennis players. These results, combined with the fact that divers, similar to many athletes in open-skill sports, must perform complex movements under high time pressure, suggest that the efficient information processing conferred by their cognitive advantages affects subsecond-duration processing, which is considered to be dominated by automatic or unconscious mechanisms.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have suggested that long periods of practice are required for unconscious or implicit learning (Lewicki, Czyzewska & Hoffman, 1987;Wulf & Schmidt, 1997).With the masked priming paradigm, recent studies found that athletes exhibit stronger unconscious response priming effects than non-athletes in a sport-specific domain, suggesting that athletes show superior unconscious information processing owing to their extensive specialized training (Gueldenpenning et al, 2015;Meng et al, 2019). However, whether athletes also show superior unconscious information processing in the general domain is still unknown.…”
Section: Introductionmentioning
confidence: 99%